PTU-050 Modifiable risk factors for gastro-oesophagal reflux disease: a mendelian randomisation study. (June 2019) - Green, Harry; Beaumont, Robin; Jones, Samuel; Yaghootkar, Hanieh; Wood, Andrew; Goodhand, James; Kennedy, Nicholas; Ahmad, Tariq; Frayling, Timothy; Weedon, Michael; Tyrrell, Jessica
Abstract : Introduction: Gastro-oesophageal Reflux Disease (GORD) is a common condition in which acid from the stomach leaks to the oesophagus causing heartburn and unpleasant taste in mouth, potentially leading to Barrett's Oesophagus and Oesophageal Adenocarcinoma. Observationally, it has been reported that low body mass index (BMI), high BMI, past smoking, alcohol and caffeine consumption increase risk of GORD. Recently, it was reported that waist hip ratio (WHR) was a better measure of obesity than BMI for predicting GORD. However, observational relationships may be affected by bias and confounding. Methods: We used data from 379, 713 unrelated European participants in the UK Biobank, including 23, 123 GORD cases to firstly explore the observational associations between GORD and adiposity measures, smoking status and smoking frequency, alcohol and caffeine consumption. We then used one- and two-sample Mendelian Randomisation (MR) techniques to test the causal relationship between the predictors and GORD. MR is a genetic technique which uses genetic variation to examine the causal effect of a risk factor on an outcome through the use of a genetic instrument for the risk factor. Results: Observationally male gender, age, past smoking, current smoking, higher BMI, higher WHR, higher body fat percentage and waist circumference associated with higher odds of GORD, whilst higher caffeinated coffee consumption was associated with lower risk of GORD. There was some tentative evidence of a J-shaped relationship between BMI and GORD. Alcohol consumption was not associated with GORD. MR provided strong evidence of a causal role for WHR, with a one-SD higher WHR causing a 1.34 higher odds of GORD (95%CI: 1.16–1.55, p= 5e-5 ). Similarly, a one-SD higher WHR adjusted for BMI was associated with 1.21 higher odds of GORD (95%CI: 1.14–1.29, p= 2e-9 ). However, there was no evidence of a causal relationship for BMI (OR: 1.00 (95%CI: 0.09–1.12), p= 0.97 ). There was no evidence of a causal role for body fat percentage, smoking and caffeine. All results were robust to 2 sample MR approaches. Conclusions: The results show robust causal evidence for the link between obesity and reflux being primarily down to WHR, not BMI. These results emphasise the importance of measuring WHR when studying gastrointestinal disorders, and the importance of weight loss in reducing the risk of reflux.